Aplicación de tres agentes clarificantes Yausa (abutilon insigne p.) gelatina y bentonita para clarificar el vino de Uvilla (physalis peruviana l.) en el emprendimiento de la parroquia de Canchagua. - Berrazueta Guilcatoma, Juan Pablo (2018)
The aim of this integration project is to apply three clarifying agents yausa (Abutilon insigne P. ) gelatine and bentonite to clarify the wine of uvilla (Physalis peruviana L. ) in the undertaking of the parish of Canchagua. This association has the need to market a quality product or a product. In addition, this project aims to control production processes in order to standardize. The must was initially adjusted to 21 º Brix to have an alcohol content of 12% in order to produce a quality wine. It was established that the acidity should be between 0.49 – 0,55%, being these the optimum values for a good fermentation. The turbidity of the wine was evaluated by the application of clarifying agents such as yausa (Abutilon insigne P. ), gelatine and bentonite compared to a control without a clarifying medium to identify improvements to the final product. The results of the project were: The control 69. 2 NTU, the mucilage of yausa 44. 4 NTU, gelatine 41. 4 NTU and bentonite 27. 6 NTU so bentonite was the best method of clarification therefore the wine was sent with the best clarifying agent to an accredited laboratory LA CONAL (food control and analysis laboratory) in which physical, chemical and microbiological analysis was performed. The results obtained showed that they are within the parameters established in the NTE INEN 374 standard for alcoholic beverages. Fruit wine 2016 . It can be concluded that our integration project successfully contributed to the improvement of the finished product of the association of the parish of Canchagua, since this wine is suitable for human consumption. Training was provided in the correct use of equipment such as the alcohol meter, portable refractometer, Ph-meter, acidometer, etc., as well as good hygiene practices to avoid contamination of the final product.